2012
DOI: 10.1002/glia.22298
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of polarization properties of human adult microglia and blood‐derived macrophages

Abstract: Both microglia, the resident myeloid cells of the CNS parenchyma, and infiltrating blood-derived macrophages participate in inflammatory responses in the CNS. Macrophages can be polarized into M1 and M2 phenotypes, which have been linked to functional properties including production of inflammation association molecules and phagocytic activity. We compare phenotypic and functional properties of microglia derived from the adult human CNS with macrophages derived from peripheral blood monocytes in response to M1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
385
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 424 publications
(399 citation statements)
references
References 42 publications
(53 reference statements)
13
385
0
1
Order By: Relevance
“…For example, some in vitro studies have suggested that human microglia develop polarization responses that are distinct from macrophages and show a tendency to maintain M2 properties under stimulation. 42 Validation of these observations in vivo in TBI is, however, difficult at the present time because of the paucity of specific markers to distinguish microglia from macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some in vitro studies have suggested that human microglia develop polarization responses that are distinct from macrophages and show a tendency to maintain M2 properties under stimulation. 42 Validation of these observations in vivo in TBI is, however, difficult at the present time because of the paucity of specific markers to distinguish microglia from macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, M1 and M2 macrophages express different repertoires of phagocytic receptors and may show differential efficiency of endocytosis and phagocytosis (18,19). It appears that the effect of macrophage polarization on phagocytosis is target dependent: M1 macrophages show enhanced phagocytosis of S. aureus (20), while M2 macrophages are more phagocytic toward myelin (21), apoptotic cells, and latex beads (22). The development of T cell-based immune responses requires days to weeks and would not be immediately provoked by exposure to particles.…”
Section: Introductionmentioning
confidence: 99%
“…The M2 anti-inflammatory phenotype has been related with the production of anti-inflammatory cytokines and is associated with regeneration properties and wound healing Zhang 2015, Ransohoff andPerry 2009). Furthermore, the M2 phenotype resolution and regenerative properties have been related with inducing OPCs differentiation, remyelination and promoting myelin clearance (Durafourt et al 2012, Kotter et al 2006, Miron et al 2013, Wang et al 2015, Yu et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…These cells are readily polarized to a M1 phenotype by incubation 71 with LPS (10-100 ng/ml)+IFNγ (20 ng/ml) and to a M2 phenotype by incubation with IL-4 (10-20 ng/ml) (Classen et al 2009). These conditions were used as controls of phenotypic changes for 24h the morphology of cells changed from a more rounded/amoeboid type to an elongated shape similar to that acquired when BMDM are treated with IL-4 (Durafourt et al 2012, McWhorter et al 2013, Vereyken et al 2011). …”
Section: Treatments That Increase Cgmp Induce Phenotype Changes In Bmdmmentioning
confidence: 99%
See 1 more Smart Citation